Current achievements and the future direction of electrochemical CO2 reduction: A short review. Issue 8 (17th April 2020) - Lee, Mi-Young; Park, Ki Tae; Lee, Wonhee; Lim, Hyungseob; Kwon, Youngkook; Kang, Seoktae
Abstract: Electrochemical CO2 reduction (CO2RR) has received much attention for its ability to generate value-added chemicals from a molecule that would otherwise be a waste end-product. Numerous studies have emerged in the past decades, but the renewable and sustainable carbon-neutral CO2 reduction process is yet to be industrialized. Here, we review the progress and bottlenecks of the electrochemical CO2 reduction technologies over the past 15 years (2004–2018) to examine whether CO2RR process is to be applicable in a large-scale. Although the techno-economic analysis and pilot plants based on liquid-phase electrolysis have shown some positive results, current densities of the liquid-phase electrochemical CO2 reduction are well below what techno-economic analyzes have projected due to its intrinsic limitations of solubility. On the other hand, the gas-phase electrolysis of CO2 has shown superior performance parameters compared to the liquid-phase electrolysis, especially in the current densities, showing commercial viability although its techno-economic analysis is yet to be performed. Herein, we offer some perspectives and guidelines where future research in CO2 electrolysis should aim. Based on the performance parameters obtained from the lab-scale gas-phase reactions, we believe that the current negative outlooks towards the industrial feasibility of the CO2 electrolysis system could turn to positive views.